Baicalin ameliorates APEC-induced intestinal injury in chicks by inhibiting the PI3K/AKT-mediated NF-κB signaling pathway - Xinyi Cheng (Elsevier, 2022)
ABSTRACT: Avian pathogenic Escherichia coli (APEC) is the causative agent of avian colibacillosis. Baicalin (BA) possesses multiple pharmacological effects, but the mechanism underlying its activity in APEC-induced intestinal injury remains unknown. This study aims to investigate the protective effects and possible mechanism of BA against APEC-induced intestinal injury. Sixty 1-day-old chicks were randomly divided into 4 groups: the control group (basal diet), E. coli group (basal diet), BAI10 group (10 mg/kg BA), and BAI20 group (20 mg/kg BA). After pretreatment with BA for 15 d and subsequent induction of APEC infection by pectoralis injection, the ileum was collected and analyzed. The results showed that BA-pretreatment demonstrated an alleviation of chicks in diarrhea rate, mortality, and histopathological changes in intestinal tissues after APEC infection. Additionally, following APEC infection, BA improved the intestinal barrier by elevating zona occludens (ZO)s (ZO-1, 2, 3), Claudins (Claudin1, 2, 3), Occludin, avian β-defensin (AvBD)s (AvBD1, 2, 4), lysozyme (Lyz) mRNA levels and ZO-1, Claudin1, and Occludin protein levels. Besides, the activities of total superoxide dismutase (T-SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and the SOD-1 and CAT mRNA levels and SOD-1 protein level were elevated by BA pretreatment. BA pretreatment also decreased the malondialdehyde (MDA) content, heme oxygenase-1 (HO-1) and NADH quinone oxidoreductase 1 (NQO1) mRNA levels, and HO-1 protein level after APEC infection. BA alleviated the APEC-induced inflammatory response, including downregulating the mRNA levels of proinflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin [IL]-1β, IL-6, IL-8) and upregulating the mRNA levels of anti-inflammatory cytokines (IL-4, IL-10, IL-13, transforming growth factor-β [TGF-β]). Furthermore, BA decreased the mRNA and protein levels of phosphatidylinositol 3 kinase (PI3K), protein kinase B (AKT), and nuclear factor kappa-B (NF-κB) as well as the expression of the phosphorylated forms of these proteins after APEC infection. Collectively, our findings indicate that BA exerts a protective effect against APEC-induced intestinal injury in chicks by inhibiting the PI3K/AKT-mediated NF-κB pathway, suggesting that BA may be a potential therapeutic approach for avian colibacillosis.